Curing or causing? HIV/AIDS in health care system of Punjab, Pakistan. - Muhammad Ahmed Abdullah; Babar Tasneem Shaikh; Haider Ghazanfar (PLoS ONE)
Background Pakistan's National AIDS Control Program has registered 44,000 HIV/AIDS patients to date, but the actual number of cases have been estimated to be as high as 150,000-170,000. The health care system has a very important role to play in this equation and must be reformed to improve the health care services in Pakistan, with regards to HIV/AIDS. Methods It was a qualitative research employing a phenomenological approach. The principal researcher visited nine public and private health care facilities and conducted 19 key informant interviews with people working for providing preventive and curative services, in addition to the observations made on the site. Results Pakistan's health system has a limited capacity to address the HIV spread in the country, with its current resources. There is an obvious scarcity of resources at the preventive, diagnostic and curative level. However, menace can be curtailed through measures taken at the service delivery level by checking the unsafe needles practices, unclean surgical procedures and an unregulated and untrained private health workforce which are dangerous potentials routes of transmission of the virus to the general population. Healthcare establishments carry the chances of nosocomial infections including HIV/AIDS. Poverty, illiteracy and stigma associated with the disease is compounding the overall situation. Conclusion Improved accessibility to service delivery with a greater focus on prevention would be imperative to address the threat of HIV/AIDS in Pakistan. A health systems approach would help in identifying gaps at both strategic and operational levels, and concurrently find and implement solutions.